(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Although ultrasound phacoemulsification (phaco) is a common method for removing a cataract for different lens densities, the phaco of a high-density nucleus remains an important issue. This is primarily associated with the technical difficulties of removing the high-density nucleus when it is impossible to break it up completely. Purpose. To determine and compare the forces required for improved and conventional phaco needles to penetrate the isolated dense crystalline lens in vitro. Materials and Methods. The experimental study involved 15 crystalline lenses from patients who had undergone a conventional extracapsular cataract extraction. Two phaco needles, a conventional phaco needle (INTREPID® Micro-Coaxial System) and an improved one (Patent of Ukraine for the useful model No. 64851), were used in experiments. Results. In the in vitro experimental study, it was established that the mean force measurement value for the improved phaco needle was 1.4 times lower than that for the conventional needle. Conclusion. The use of the improved needle for the phaco of a high-density nucleus is reasonable and makes it possible to penetrate deeply into the lens and divide the lens into fragments in a prompter and more efficacious manner than with the use of the conventional phaco needle.